Review of Black Soldier Fly (Hermetia illucens) as Animal Feed and Human Food - Yu-Shiang Wang; Matan Shelomi (Foods, 2017)
Food futurists accept that sustainability-minded humanity will increasingly incorporate insects as alternative protein. The most studied and easily reared species are not necessarily the most sustainable, acceptable, or delicious. Here, we review the literature on the black soldier fly, Hermetia illucens, which is capable of efficiently converting a wide variety of organic materials, from food waste to manure, into insect biomass. They can be grown and harvested without dedicated facilities and are not pestiferous. Their larvae are 42% crude protein and 29% fat, although they are higher in saturated fats than most insects. They do not concentrate pesticides or mycotoxins. They are already grown and recommended for use as animal feed, but with regional legal restrictions on how this is done. For commercial use in human foods, larvae could potentially be milled and converted into a textured protein with a strong flavor. Their biggest advantage over other insects is their ability to convert waste into food, generating value and closing nutrient loops as they reduce pollution and costs. This general advantage is also their greatest disadvantage, for the social stigmas and legal prohibitions against eating organisms that eat waste are added to extant taboos facing insect consumption.